Inside the Canberra Press Gallery Life in the Wedding Cake of Old Parliament House - Chalmers, Rob (ANU Press, 2011)
Before television, radio, and later the internet came to dominate the coverage of Australian politics, the Canberra Press Gallery existed in a world far removed from today's 24-hour news cycle, spin doctors and carefully scripted sound bites. This historical memoir of a career reporting from The Wedding Cake of Old Parliament House offers a rare insider's perspective on both how the gallery once operated and its place in the Australian body politic. Using some of the biggest political developments of the past fifty years as a backdrop, Inside the Canberra Press Gallery - Life in the Wedding Cake of Old Parliament House sheds light on the inner workings of an institution critical to the health of our parliamentary democracy. Rob Chalmers (1929-2011) entered the Federal Parliamentary Press Gallery in 1951 as a twenty-one-year-old reporter for the now-defunct Sydney Daily Mirror and would retire from political commentary 60 years later - an unprecedented career span in Australian political history. No parliamentary figure - politician, bureaucrat or journalist − can match Chalmers' experience, from his first Question Time on 7 March 1951 until, desperately ill, he reluctantly retired from editing the iconic newsletter Inside Canberra sixty years, four months and eighteen days later. As well as being considered a shrewd political analyst, Chalmers was a much-loved member of the gallery and a past president of the National Press Club. Rob Chalmers used to boast that he had outlasted 11 prime ministers; and a 12th, Julia Gillard described him as 'one of the greats' of Australian political journalism upon his passing. Rob Chalmers is survived by his wife Gloria and two children from a previous marriage, Susan and Rob jnr.